2000
DOI: 10.1063/1.126774
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Si doping on optical characteristics of cubic GaN grown on (001) GaAs substrates

Abstract: The photoluminescence (PL) properties of Si-doped cubic GaN with different carrier concentrations were investigated at room temperature. The epilayers were grown on GaAs (001) by radio-frequency molecular-beam epitaxy. It was found that when the carrier concentration is increased from 5×1015 to 2×1018 cm−3, the PL peak shifted towards low energy, from 3.246 to 3.227 eV, and the PL linewidth increased from 77.1 to 121 meV. The PL peak shift is explained by the band gap narrowing effect due to the high doping co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 17 publications
0
8
0
Order By: Relevance
“…17 The maximal change of the DBE peak energy was found to be as large as 6 meV at the maximal doping level of 8.8 × 10 17 cm −3 in our samples. This result can be explained by the band gap narrowing (BGN).…”
Section: Resultsmentioning
confidence: 90%
“…17 The maximal change of the DBE peak energy was found to be as large as 6 meV at the maximal doping level of 8.8 × 10 17 cm −3 in our samples. This result can be explained by the band gap narrowing (BGN).…”
Section: Resultsmentioning
confidence: 90%
“…These considerations show that Si and O may be the elements most appropriate for n-type doping of GaN. Doping of MBE grown c-GaN by Si was reported by As et al [50], Martinez-Guerrero [51] and Li et al [52]. Elemental Si was evaporated from an effusion cell at source temperatures between 750 °C and 1200 °C.…”
Section: N-type Dopingmentioning
confidence: 91%
“…With increasing Si doping, it has been reported that the exciton emission peak shifted to lower energies with an accompanying increase in its width. 462,463 For impurity concentrations near 10 20 cm −3 , band-to-band transitions dominated in degenerate GaN:Si at low temperatures. 463 The 3.15-eV band, assigned to DAP transitions involving an unidentified shallow acceptor, exhibited a shift to higher energies with increasing Si doping.…”
Section: Silicon Dopingmentioning
confidence: 99%